Toxicological Characterization of GHB as a Performance-Enhancing Drug - Giorgetti, Arianna; Busardò, Francesco Paolo; Giorgetti, Raffaele (Frontiers in Psychiatry, 2022)
Performance-enhancing drugs (PEDs) are represented by several compounds used to ameliorate the image, the appearance, or an athletic or non-athletic performance. Gamma-hydroxybutyrate (GHB) is an endogenous molecule first used as anesthetic and then marketed as a nutritional supplement with a wide diffusion in the bodybuilding community. The aim of the present work is to provide a toxicological characterization of the use of GHB as a PED, including the scientific basis for its use, the patterns of use/abuse, and the health risks arising from its consumption in this peculiar recreative setting. A literature search was performed on multiple databases including experimental studies on humans and animals as well as epidemiological reports and forensic case reports/series. Experimental studies demonstrated that the use of GHB as a PED is motivated by the release of growth hormone and the induction of sleep. However, the panel of desired performance-related effects was much wider in real cases and epidemiological studies. Even though the use of GHB among bodybuilders has decreased, its use to enhance some kind of performance, particularly sexual ones or social-communicative ones, as well as means to increase mood and perceived energy, is still common.